2012
DOI: 10.4161/psb.22015
|View full text |Cite
|
Sign up to set email alerts
|

The role of carbon in fungal nutrient uptake and transport

Abstract: T he arbuscular mycorrhizal (AM) symbiosis, which forms between plant hosts and ubiquitous soil fungi of the phylum Glomeromycota, plays a key role for the nutrient uptake of the majority of land plants, including many economically important crop species. AM fungi take up nutrients from the soil and exchange them for photosynthetically fixed carbon from the host. While our understanding of the exact mechanisms controlling carbon and nutrient exchange is still limited, we recently demonstrated that (i) carbon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Future studies on the impacts of global change on grassland ecosystems should focus on the interactions between plant species and fungal communities. Nevertheless, our findings provide a compelling evidence to support the hypothesis that that the host plants are in control of AMF–plant symbiosis (Fellbaum, Mensah et al., ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Future studies on the impacts of global change on grassland ecosystems should focus on the interactions between plant species and fungal communities. Nevertheless, our findings provide a compelling evidence to support the hypothesis that that the host plants are in control of AMF–plant symbiosis (Fellbaum, Mensah et al., ).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, 7-year N addition at a rate 40 kg ha −1 year −1 reduced AM fungal spore density, species richness and extraradical hyphal lengths in four functional groups (C 3 grasses, C 4 grasses, forbs and legumes) in North American tallgrass prairies (Antoninka, Reich, & Johnson, 2011). In contrast, the N addition had little effects on spore abundance in forbs and extraradical hyphal length in C 4 grasses and legumes in the tallgrass prairies of their photosynthetically fixed C to their associated AM fungi (Fellbaum, Mensah et al, 2012;Johnson, 2010;Smith & Read, 2008;Wright, Read, & Scholes, 1998). In this study, we found that N addition significantly reduced the photosynthetic rate and root/shoot ratio in A. frigida, while N addition had no impact on photosynthetic rates and root/shoot ratio in S. krylovii (Figures 5 and 7c).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We speculate that this could indicate a phosphorus-dependent shift in the underlying exchange relationships between photosynthetic plants and their AM fungal partners. Although elucidation of the exact mechanism falls outside the scope of this study, we hypothesize that such a functional shift could be underpinned by a reduction in carbon allocation from photosynthetic plants to AM fungal partners at increasing concentrations of soil phosphorus [47], either inhibiting the release of chemical factors from the fungi that stimulate the germination of mycoheterotrophs [48], or causing the fungi to restrict carbon flow to mycoheterotrophs [49]. Alternatively, it could be that changes in AM fungal community dynamics (such as competition) at elevated soil phosphorus (indicated by changes in soil AM fungal community composition; figure 4) may affect mycoheterotroph abundance.…”
mentioning
confidence: 99%
“…The increase in the P capacity of the plants can be attributed to the large increase in soil exploration area (more than one hundred times) due to mycorrhizal external mycelium production, its greater efficiency of nutrient absorption and higher affinity (lower Km) for P uptake from the soil solution. More recent work demonstrated that C also acts as a trigger for fungal N and K uptake and transport [11]. N in the soil had high mobility to move to plant roots through mass flow, therefore it had been suggested that the AMF played little role in N uptake.…”
Section: Kinetic Parametersmentioning
confidence: 99%